Efectos de Bacillus spp. en organismos no diana del ecosistema terrestre - Castañedo Hernández, Zoe Alicia (2024)
The increase in the world population brings with it the need for food production and therefore the search for technological alternatives to satisfy this demand. According to the Food and Agriculture Organization of the United Nations (FAO), it is necessary to evaluate both the effectiveness and the safety of all products used in agriculture. The Institute of Plant Biotechnology of the province of Villa Clara, Cuba, immersed in the solution of this problem, has shown that two biopreparations CCIBP-C5 (Bacillus pumilus) and CCIBP-A5 (Bacillus amyloliquefaciens) have an effect on plant growth and activity against phytopathogenic fungi. However, there is no evidence of its safety on non-target organisms in the ecosystem. Terrestrial ecotoxicology is the branch of science devoted to predicting said impact on representative organisms. Four tests were carried out to evaluate the acute toxicity of Bacillus species at concentrations of 108 UFC.g-1 of soil, according to the regulations of the United States Environmental Protection Agency (EPA) in the biomodels of Eisenia fetida and different species of terrestrial plants. Mortality/germination inhibition, weight, vegetative vigor and other clinical findings were investigated for 30 days. There was no mortality in any of the biomodels and the observed effects did not show significant statistical differences with the corresponding control group. We can conclude that the CCIBP-C5 and CCIBP-A5 biopreparations are not toxic to the species studied in the terrestrial ecosystem.